Development Of Ph-Sensitive Gelatin-Based Intelligent Film Incorporating Dragon Fruit Skin Powder - Azlim, Nurnabila Afiqah (Universiti Sains Malaysia, 2020)
In this study, gelatin-based intelligent film incorporating anthocyanin from dragon fruit skin (DFS) powder (Hylocereus polyrhizus) was prepared as an indicator for food freshness. It was developed to evaluate the effects of DFS powder on its mechanical properties, moisture sorption properties and also the pH sensitivity properties of the films. The films were made by using the casting technique and labeled as dragon fruit bovine gelatin (DFBG) according to the different extraction content. DFBG films were characterized by Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The moisture content, mechanical properties, water solubility, water vapour permeability, light transmittance, color and pH-sensing evaluations were determined to evaluate its potential applications. FTIR spectroscopy revealed that the anthocyanin in the extract can interact with the other film components through the hydrogen bonds. SEM also presented that with the addition of the extract, the films exhibited to be smooth and give a clear surface to the films. The incorporation of anthocyanin from DFS powder had increased the moisture content, thickness and water solubility of the films, but decreased the tensile strength, water vapour permeability and light transmittance of the films. The films showed to give larger ΔE with an increased amount of the extract indicated that the films produced good color variability. However, no significant changes happened when the films were exposed to different pH buffer solutions. More buffer solutions were needed in order to observe the color changes of the films. This study, therefore, indicated that DFBG3 film which showed to give good results can be used to monitor the freshness of food.